Women with borderline personality disorder do not show altered BOLD responses during response inhibition. Issue 3 (30th December 2015) - van Eijk, Julia; Sebastian, Alexandra; Krause-Utz, Annegret; Cackowski, Sylvia; Demirakca, Traute; Biedermann, Sarah V.; Lieb, Klaus; Bohus, Martin; Schmahl, Christian; Ende, Gabriele; Tüscher, Oliver
Abstract: Impulsivity is central to borderline personality disorder (BPD). Response inhibition, addressing the ability to suppress or stop actions, is one aspect of behavioral impulse control which is frequently used to assess impulsivity. BPD patients display deficits in response inhibition under stress condition or negative emotions. We assessed whether response inhibition and its neural underpinnings are impaired in BPD when tested in an emotionally neutral setting and when co-morbid attention-deficit/hyperactivity disorder (ADHD) is excluded. To this end, we studied response inhibition in unmedicated BPD patients and healthy controls (HC) in two independent samples using functional magnetic resonance imaging during Simon-, Go/nogo-, and Stopsignal tasks. BPD patients and HC did not differ significantly in their performance in the Go/nogo and the Stopsignal tasks. Response interference in the Simon task was increased in BPD patients in one sample, but this could not be replicated in the second sample. In both samples, no significant differences in brain activation patterns during any of the tasks were present while the neural impulse control network was robustly activated during the inhibition tasks in both groups. Our results provide evidence that under emotionally neutral conditions response inhibition is not impaired in patients with BPD without co-occurring ADHD. Highlights: Response inhibition is studied in a series of experiments in BPD patients and HC. No performance group differences in Go/nogo and Stopsignal tasks were observed. No group differences in fMRI BOLD signal during response inhibition were present. Emotionally neutral response inhibition is not impaired in BPD patients. Neutral response inhibition tasks do not adequately capture BPD typical impulsivity.